A qualitative study on wife abuse in Muslim families: why women endure? / Mariny Abdul Ghani, Noor Azizah Ahmad and Azizul Mohamad - Abdul Ghani, Mariny; Ahmad, Noor Azizah; Mohamad, Azizul (2015)
Malaysia is an Islamic country with more than half of its population embracing the religion of Islam. In relation to this, the requirement of understanding the Islamic approach on various aspects of its people lives is pivotal. This includes the teachings on the structure of the Muslim family. According to the Islamic view, marriage entails certain obligations, rights and duties between a husband and wife. These foundations have been laid for the couples to achieve a happy marriage as well as to enjoy a stable married life equally. Previous studies have shown that the prevalence of domestic violence in Muslim societies is comparable to that of Western countries where the research data in Egypt, Palestine and Tunisia shows that the occurrence of domestic violence is 1 in 3 women. Domestic violence can be seen as nusyuz or a careless attitude towards responsibilities between husband and wife, without any unlawful reasons which are solemnized by the Sharia Law. Islam prohibits the husband to use any form of violence against the wife when disagreements arise. This paper attempts to elaborate the impact of wife abuse and also identify the barriers that make the women unable to disclose the violence; from their perspectives as a Muslim. The study employs qualitative interviews with 25 women who identified themselves as victims and survivors of domestic violence. The findings indicate that the women perceived of wife abuse as strengthening their faith in destiny, however their understanding on Islamic concepts about being 'a good wife' is in vital need of rectification.